Expansion of the clinical and molecular spectrum of an XPD‐related disorder linked to biallelic mutations in ERCC2 gene. Issue 6 (5th April 2021) - Agolini, Emanuele; Botta, Elena; Lodi, Mariachiara; Digilio, Maria Cristina; Rinelli, Martina; Bellacchio, Emanuele; Alesi, Viola; Nardo, Tiziana; Zambruno, Giovanna; Orioli, Donata; Alessi, Iside; Boccuto, Luigi; et al.
Abstract: Bi‐allelic inactivation of XPD protein, a nucleotide excision repair (NER) signaling pathway component encoded by ERCC2 gene, has been associated with several defective DNA repair phenotypes, including xeroderma pigmentosum, photosensitive trichothiodystrophy, and cerebro‐oculo‐facio‐skeletal syndrome. We report a pediatric patient harboring two compound heterozygous variants in ERCC2 gene, c.361‐1G>A and c.2125A>C (p.Thr709Pro), affected by severe postnatal growth deficiency, microcephaly, facial dysmorphisms and pilocytic astrocytoma of the brainstem. Some of these features point to a DNA repair syndrome, and altogether delineate a phenotype differentiating from disorders known to be associated with ERCC2 mutations. The DNA repair efficiency following UV irradiation in the proband's skin fibroblasts was defective indicating that the new set of ERCC2 alleles impacts on NER efficiency. Sequencing analysis on tumor DNA did not reveal any somatic deleterious point variant in cancer‐related genes, while SNP‐array analysis disclosed a 2 Mb microduplication involving the 7q34 region, spanning from KIAA1549 to BRAF, and resulting in the KIAA1549:BRAF fusion protein, a marker of pilocytic astrocytoma. In conclusion, this report expands the clinical and mutational spectrum of ERCC2 ‐related disorders. Abstract : We describe a patient harboring two compound heterozygous variants in ERCC2 gene, affected by severe postnatal growth deficiency, microcephaly, facial dysmorphisms and pilocytic astrocytoma of the brainstem . The present report expands the clinical and mutational spectrum of ERCC2 ‐related disorders.